Health and productivity benefits of a multicomponent workplace program by gender in small companies - Jiménez Díaz-Benito, Víctor; Bonal, Jose; Fernandez-Luna, Alvaro; Burillo, Pablo; Macías, Ricardo; León-Quismondo, Jairo (Frontiers in Sports and Active Living, 2025)
BackgroundPhysical inactivity is a major public health concern, with persistent gender disparities and growing sedentary behavior in modern workplaces. Small- and medium-sized enterprises (SMEs), despite employing most of the workforce, often lack structured health programs. Workplace physical activity interventions show promise but yield mixed results, especially when gender differences are not considered. This study addresses these gaps by evaluating a supervised exercise program through a sex-disaggregated analysis in SMEs from diverse sectors.MethodsWe conducted a 12-week multicomponent physical activity program in three SMEs, using a mixed factorial design to assess changes by time, gender, and company. Physically inactive employees with sedentary jobs participated in supervised exercise sessions and health-promotion activities. The study included employees from three sectors: Training and Consulting, Insurance and Technology, and Digital Engineering, with a total sample of 49 participants (41 women and 8 men). Pre-and post-intervention measures included anthropometrics, perceived health, cardiorespiratory fitness, and productivity.ResultsCardiovascular fitness improved significantly in both sexes, and diastolic blood pressure decreased over time across companies. Quality-of-life scores did not improve globally. Productivity costs due to presenteeism decreased significantly, with post hoc differences by company and sex (p < .001).DiscussionA tailored three-month supervised exercise program, delivered onsite or online three times per week, appears to improve health outcomes among SME administrative staff and reduce productivity losses, especially when combining aerobic and strength training with activation routines, workshops, and gamified challenges.